Abscopal effect-induced spontaneous regression of distant metastases in malignant mesenchymal tumor: a case report - Meltem Kirli Bolukbas; Cemile Ozdemir; Esengul Kocak Uzel (Frontiers in Oncology)
The abscopal effect refers to an anti-tumor response that occurs in areas where radiotherapy (RT) has not been directly administered but is triggered by the immune system. We presented a case of an undifferentiated pleomorphic sarcoma with three relapses that showed a complete response after distant metastatic disease. The tumor was initially detected in the left pectoral muscle. Fifteen months after adjuvant RT and chemotherapy, a nearby recurrent lesion was surgically removed. Another 15 months later, a second recurrence appeared on the left lateral chest wall. The patient underwent a third surgery and received adjuvant radiation, but distant metastases were discovered 6 months later. Shortly after a biopsy confirmed distant metastasis, all metastatic foci went into spontaneous remission. This phenomenon is identified as the abscopal effect. The patient experienced no metastasis or local recurrences during follow-up and showed a complete response to the abscopal effect for 36 months. The abscopal effect in malignant mesenchymal tumors is extremely rare.